Between two Worlds - "Caldwell, Lynton Keith" (New York, 1990)
There is no simple answer to the question of whether we as humans can adapt our lifestyles in the pursuit of an environmentally sound world. Inadequate information is a limiting factor, and unforeseen events make uncertainty inevitable. Even so, choices made today can narrow or expand future options. A critical task for society today is to reverse trends that narrow these options, a task in which science plays a vital role. In his thought-provoking book, Dr. Caldwell attempts to address this issue with an integrated analysis of the interrelationships among science, the environmental movement, and public policy. Special emphasis is given to the interactions of environmentalism and science in generating public and international environmental policies.
Keywords: Environmental policy